Optimizing language literacy in students with visual impairment through storytelling training - Triandari, Asyifa Putri; Anwar, Rully Khairul; Lusiana, Elnovani (Jurnal Informatio, 2026)
Background: The low level of literacy, especially among students with visual impairment in Indonesia, is a serious problem that requires special attention. In fact, literacy is a fundamental skill that is essential for every individual, from birth, to participate fully in society. One of the special schools that implements literacy activities to encourage language literacy skills among its students is SLB Negeri A Pajajaran in Bandung, which provides extracurricular activities in the form of storytelling training.Purpose: This study aimed to analyze the application of storytelling training in optimizing the language literacy skills of visually impaired children at SLBN A PajajaranMethods: This research uses a qualitative method with case study approach. Data were obtained through observation, interviews, literature review, and documentation. Data were analyzed using Bandura’s social learning theory and Vygotsky’s cognitive development theory.Results: The storytelling training extracurricular at SLBN A Pajajaran in elementary school level is conducted by having students listen to an audio recording to memorize, practice, and then receive evaluation from the supervising teacher.Conclusions: This activitiy not only hones students’ literacy skills, such as listening, speaking, reading, writing, expressing opinions, and training them to think structurally in the class, but also has a long-term impact in the future such as social self confidence. Future research could conduct studies with the same topic and research subject, but with a greater focus on the effectiveness using a braille book versus an audiobook.